Drug utilisation in medical intensive care unit: a retrospective analysis from a tertiary care teaching hospital - R., Arathy; Chacko, Jiyo; Pillai, Santosh; Bhanu, Anish; Raphael, Ruby; M., Jalajakumari (International Journal of Basic & Clinical Pharmacology, 2017)
Background: The World Health Organisation has defined drug utilization study as “the marketing, distribution, prescription and use of drugs in a society, with special emphasis on the resulting medical, social, and economic consequences. The objective was to evaluate drug utilization pattern in medical intensive care unit (MICU) in a tertiary care teaching hospital. Methods: A retrospective observational study was conducted in MICU for adult patients admitted from October to December 2013. Data collected was analysed for demographics, indication, duration of stay, World Health Organisation (WHO) prescribing indicators including anatomical therapeutic chemical classification and defined daily dose (DDD). Results: A six hundred encounters from 63 male and 44 female patients with a mean age of 60.88±16.87 were studied. Average duration of stay was 5.61±3.88 days. The common indications for admission were dyspnoea 20 (18.69%), upper gastrointestinal bleed 16 (14.95%), cerebrovascular accident 14 (13.08%) and sepsis 13 (12.15%). Total number of drugs prescribed was 246. Total drug encounters were 7695. Average number of drugs per encounter was 12.83. Percentage of drugs prescribed by generic name was 38.21%, 44.7% and 40.65% of the drugs were prescribed from National and WHO essential medicine list respectively. Among the drugs prescribed 65.44%, 32.93% and 17.48% were oral, injectable and fixed dose combination preparations respectively. Percentage of encounters resulting in prescription of an antibiotic and an injection were 59% and 85.83% respectively. The most commonly prescribed drugs were pantoprazole (100%), human regular insulin (52.83%), piperacillin + tazobactam (45%) and ceftriaxone (38%). Their DDD/100 bed days were found to be 83.79, 12.78, 12.50, and 17.81 respectively. Conclusions: Overall the prescribing pattern seems to be rational but may be further strengthened by increasing generic drug prescription, judicious use of pantoprazole and periodic longitudinal surveillance studies.